STRATEGI MANAJEMEN LINGKUNGAN DALAM RANGKA PENURUNAN KANDUNGAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) PT. PINDO DELI, KARAWANG - Johanes Hendra (Jurnal Green Growth dan Manajemen Lingkungan, 2013)
The need for paper today continues to increase, economic growth also means increased forward to improve. The production of industrial paper in National and International market (export) so as to encourage paper mills continue to increase its production. Indonesian paper production in 2011 reached more than 11 million tons. All these activities will result in a positive or negative nature. One of the negative impact that a "focus" is the Pollution of Surface Water / Water River. Since 2005 has recorded more than 62 Watershed (DAS) in a critical condition. The paper industry needs clean water as a raw material of about 10-30 mÂ³/ton paper, waste water thus generated is potentially polluting the river. Such a large volume of waste water and have different characteristics from other industries that require serious optimizing reduction strategy content of hazardous and toxic waste(B3).Factually the wastewater coming out of "paper machine" must be processed through the Waste Water Treatment Plant (WWTP) because as "output" it there are 2 (two) components: First ; Effluent discharge, must accept the Standards of Quality by the Government, as appropriate: Kep-51/MENLH/10/1995, Date: October 23, 1995.Second: Sludge (B3), solid waste is processed through a form of WWTP sludge with fiber content, CaCO3 and other particles carried by the waste water, Standard of Water Quality Management and Water Pollution Control : PP. no. 82 / 2001. The buildup of sludge need to swatch innovation measures that can reduce pollution / minimize the risk of the Watershed (DAS) Citarum.